Meningkatkan Daya Saing Lulusan SMK Mandiri Palembang Melalui Pendampingan Penggunaan Accurate Accounting - Mutiara Lusiana Annisa; Ruth Samantha Hamzah (PT. Altaf Publishing Corp, 2025)
This community service program was organized with the aim of enhancing the technical skills of Accounting students at SMK Mandiri Palembang through training in the use of the Accurate Accounting software. In the context of the rapidly evolving digital technology and industry demands, proficiency in accounting software has become a crucial skill that SMK graduates must possess. The program was implemented using a hands-on training and mentoring approach, which included an introduction to the basic concepts, key features of the Accurate software, as well as practical accounting simulations based on real-world cases. The results of the program showed that the majority of participants were able to understand the software's workflow and effectively operate its features, including the ability to generate financial reports automatically based on simulated transactions. In addition to enhancing technical skills, the program also contributed to building the students' confidence in facing digital work challenges. Furthermore, the initiative strengthened the collaboration between vocational education institutions and universities, creating opportunities for ongoing partnerships. Therefore, this training not only provided practical benefits in learning but also held strategic value in improving the competitiveness of SMK graduates in the era of Industry 4.0 and Society 5.0.